ANALISIS STRATEGI TOKO/RITAIL TRADISONAL DALAM PENGHADAPI MINIMARKET /RITAIL MODERN DI KABUPATEN LOMBOK TENGAH - Alamsyah Abubakar; Junaidi Sagir; Lalu Hamdani Husnan (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
The Objectives of this study were to know the strengths, weaknesses, opportunities and threats faced by traditional retailers in the face of modern minimarket. In line with that to find out the right alternative strategies in dealing with those modern minimarkets.. Type of this research is applied descriptive whereas the population consist of entrepreneurs, managers and owners of traditional shops, consumers and communities who lives around shops / minimarkets. Data collection used in this study were sample survey where 30 people as respondents. Data analyzed by Porter's five forces analysis, SWOT analysis, Internal Factor Analysis & External Factor Analysis and SPACE Matrix analysis. The results showed that the analysis of Diamond’s Porter, a traditional market (grocery store) has advantages that are supported by factor conditions, demand conditions, related and supporting industries, the role of government and opportunities. Strategies that can be recommended are 1) S-O Strategy: develop the concept of one stop shopping and keep using traditional systems, not self-service. 2) S-T Strategy: maintain and establish good relationships with customers, maintain store image and standardize services. 3) W-O's strategy maximize KUR (special credits for small enterprise) assistance and sales profit to improve shop shortages and expand the network and look for goods in cheap places. 4) W-T Strategy: improve service quality as an effort to retain customers, and make service standards. Meanwhile, based on IFAS, EFAS, and Space matrix analysis, it is found that traditional retail shops / retailers must use aggressive strategies in dealing with modern retail / shops.